Alleviating the toxicity concerns of antibacterial cinnamon‐polycaprolactone biomaterials for healthcare‐related biomedical applications. Issue 2 (18th May 2021) - Ahmed, Jubair; Gultekinoglu, Merve; Bayram, Cem; Kart, Didem; Ulubayram, Kezban; Edirisinghe, Mohan
Abstract: Fibrous constructs with incorporated cinnamon‐extract have previously been shown to have potent antifungal abilities. The question remains to whether these constructs are useful in the prevention of bacterial infections in fiber form and what the antimicrobial effects means in terms of toxicity to the native physiological cells. In this work, cinnamon extract containing poly (ε‐caprolactone) (PCL) fibers were successfully manufactured by pressurized gyration and had an average size of ∼2 μm. Cinnamon extract containing PCL fibers were tested against Escherichia coli, Staphylococcus aureus, Methicillin resistant staphylococcus aureus, and Enterococcus faecalis bacterial species to assess their antibacterial capacity; it was found that these fibers were able to reduce viable cell numbers of the bacterial species up to two orders of magnitude lower than the control group. The results of the antibacterial tests were assessed by scanning electron microscopy (SEM). The constructs were also tested under indirect MTT tests where they showed little to no toxicity, similar to the control groups. Additionally, cell viability fluorescent imaging displayed no significant toxicity issues with the fibers, even at their highest tested concentration. Here we present a viable method for the production the non‐toxic and naturally abundant cinnamon extracted fibers for numerous biomedical applications. Abstract : Cinnamon directly extracted into a polycaprolactone polymer base was spun with pressurized gyration to produce a high yield of cinnamon‐extracted bandage‐like fibers. These fibers where then characterized and tested for cytotoxity and antibacterial activity against Escherichia coli, Staphylococcus aureus, Methicillin Resistant Staphylococcus aureus and Enterococcus faecalis .